(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2026)
In this paper, a new method, Adomian homotopy method, is proposed. The method cou ples the Adomian decomposition and the homotopy perturbation methods for fast and effective results. Complications involving the application of the two methods are avoided using the new technique. Nonlinear differential equations are utilized to highlight the effectiveness and applicability of the method.